10 minute solution. Target toning for beginners [videorecording (DVD)] - Ambandos, Andrea; Whitmarsh, Cindy (Anchor Bay Entertainment, 2004)
Five targeted workouts for beginners, each focused on a specific muscle group, and each only ten minutes. Split them into five separate workouts, or do them together for a total-body workout. The workouts cover abs, thighs, buns, arms and shoulders, and powerstretch.